Bioengineering for surgery : the critical engineer-surgeon interface - Farhat, Walid A.; Drake, James M. (Cambridge, UK : Woodhead Publishing, an imprint of Elsevier, 2016)
'Bioengineering is the application of engineering principles to address challenges in the fields of biology and medicine encompassing the principles of engineering design to the full spectrum of living systems. In surgery, recent advances in minimal invasive surgery and robotics are the culmination of the work that both engineers and surgeons have achieved in the medical field through an exciting and challenging interface. This interface rests on the medical curiosity and engineering solutions that lead eventually to collaboration and development of new ideas and technologies. Most recently, innovation by surgeons has become a fundamental contribution to medical research in the surgical field, and it is through effective communication between surgeons and biomedical engineers and promoting collaborative initiatives that translational research is possible. Bioengineering for Surgery explores this interface between surgeons and engineers and how it leads to innovation processes, providing clinical results, fundraising and prestige for the academic institution. This book is designed to teach students how engineers can fit in with their intended environment and what type of materials and design considerations must be taken into account in regards to medical ideas'--Publisher's description.
Interface between engineering and medicine -- Clinical translation and commercialization -- Image fusion and visualization -- Image-guided procedures: tools, techniques, and clinical applications -- Surgical robotic tools -- Simulation in minimal access surgery -- A simulation hospital as a model of immersive-based learning: the concept and challenges -- Virtual simulation: abdomen -- Application of 3D printing in medical simulation and education -- Simulation surgical models: surgeon perspectives -- Bioengineering and regenerative medicine in surgery -- Concluding remarks.
Includes bibliographical references and index.
Description based on online resource; title from resource home page (ebrary, viewed February 23, 2016).
Elsevier
Keywords: Biomedical engineering; Biomedical engineering -- Surgery; Bioengineering -- methods; Biomedical Engineering -- methods; Surgery, Computer-Assisted -- methods; Surgical Procedures, Operative -- instrumentation; Minimally Invasive Surgical Procedures -- instrumentation; Robotics; Diagnostic imaging; HEALTH & FITNESS / Holism; HEALTH & FITNESS / Reference; MEDICAL / Alternative Medicine; MEDICAL / Atlases; MEDICAL / Essays; MEDICAL / Family & General Practice; MEDICAL / Holistic Medicine; MEDICAL / Osteopathy; Electronic books